Potassium uptake system Trk2 is crucial for yeast cell viability during anhydrobiosis. Issue 1 (11th December 2013) - Borovikova, Diana; Herynkova, Pavla; Rapoport, Alexander; Sychrova, Hana
Abstract Yeasts grow at very different potassium concentrations, adapting their intracellular cation levels to changes in the external environment. Potassium homeostasis is maintained with the help of several transporters mediating the uptake and efflux of potassium with various affinities and mechanisms. In the model yeast Saccharomyces cerevisiae, two uptake systems, Trk1 and Trk2, are responsible for the accumulation of a relatively high intracellular potassium content (200–300 mM) and the efflux of surplus potassium is mediated by the Tok1 channel and active exporters Ena ATPase and Nha1 cation/proton antiporter. Using a series of deletion mutants, we studied the role of individual potassium transporters in yeast cell resistance to dehydration. The Trk2 transporter (whose role in S. cerevisiae physiology was not clear) is important for cell viability in the stationary phase of growth and, moreover, it plays a crucial role in the yeast survival of dehydration/rehydration treatments. Mutants lacking the TRK2 gene accumulated significantly lower amounts of potassium ions in the stationary culture growth phase, and these lower amounts correlated with decreased resistance to dehydration/rehydration stress. Our results showed Trk2 to be the major potassium uptake system in stationary cells, and potassium content to be a crucial parameter for desiccation survival.